Business transformation from connectivity to digital: case study “PT. MNO Indonesia” - Fauzan, Itsnanta Muhammad; Ihsan, Amirul; Mahmudi, Farhan Annur; Mubarak, Amirsyah Rayhan; Apriono, Catur (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2022)
The telecommunications industry plays a role in meeting the needs of digital connectivity services to the community, especially in line with the community's need for internet connections which is increasing rapidly. As one of the telecommunications service operators in Indonesia, "PT. MNO Indonesia" must meet this need to get maximum profit and the best service to the customers with the right business strategy. However, the current connectivity business model is still the mainstay, with revenue levels that tend to stagnate and even experience a decline. The provision of network services and investment in infrastructure development are still the main concerns, so a change in business strategy is needed. This study proposes several recommendations for business strategies to increase revenue based on reviewing and analyzing financial data and statistics for Indonesian and international telecommunications businesses. In this study, financial report data and digital sector statistical data were analyzed and divided into four aspects: traffic, finance, network development, and digital service with the min-max method, standard deviation, and average. From the analysis conducted in this research, "PT. MNO Indonesia" needs to transform its business into digital business model.